Institutional Strategies to Achieve Gender Equity in Intercollegiate Athletics: Does Title IX Harm Male Athletes? - Anderson, Deborah J; Cheslock, John J (American Economic Review, 2004)
Institutional Strategies to Achieve Gender Equity in Intercollegiate Athletics: Does Title IX Harm Male Athletes? by Deborah J. Anderson and John J. Cheslock. Published in volume 94, issue 2, pages 307-311 of American Economic Review, May 2004